The Affective Politics of Labelling in Egypt Post-2013 - Hassan, Dina Ibrahim (AUC Knowledge Fountain, 2026)
The process and consequences of labelling groups and individuals has been a central concern for sociology and anthropology present in the writings of those considered founders of the disciplines, through development of cultural studies, criminology, and, in more recent times considerations of affect. However, little has been written about these processes and their social and political consequences outside of western contexts. This thesis focuses on how labels have been created, acquired meaning, and shaped the conditions of social and political life in Egypt since 2013. It explores the mechanisms of being labeled, named, and categorized within shifting political and cultural discourses. Through an ethnographically grounded and affectively attuned approach, this research examines the subtle mechanisms through which labels operate, circulate in public spheres, and define modes of belonging and exclusion. This study focuses on how labels are portrayed in multiple sites such as political discourse, pop culture, and the everyday.